Consistent estimates of gross primary production of Finnish forests - comparison of estimates of two process models - Peltoniemi, Mikko; Markkanen, Tiina; Härkönen, Sanna; Muukkonen, Petteri; Thum, Tea; Aalto, Tuula; Mäkelä, Annikki
2015